Jesus and Higher Order Thinking Jesus as a Great Communicator and Educator - Daniel Trihandarkha (Sekolah Tinggi Teologi Sangkakala & Sekolah Tinggi Jemaat Kristus Indonesia, 2022)
It has been analyzed with variety sets of scrutiny that Jesus’ way of communicating his message to people were effective and impactful form of communication. Those who engage with Jesus from variety background, from the beggars to the aristocrats showed how thoughtful Jesus had formulated his wording beforehand. Thus, some were challenged, encouraged, and even confronted. The communication in the perspective of Higher Order Thinking demands the listener to engage, self-examine and then decide of what to do. Jesus’ communication styles, in the from parables, sermons, exhortations, reprimands, and confrontations left no room for indifference attitude.